Geomorphological study of unstable rock slope deformation on Stáluvárri, Kåfjorden, Troms - Nypan, Iver Magnarson (UiT Norges arktiske universitet, 2024)
Unstable rock slope failures are catastrophic hazards with a long history in Norway. A large portion of these have been detected within Troms County, with a high percentage of them the Lyngenfjorden fault zone. Stáluvárri, a mountain in Kåfjord commune, is such a slope with detected bodies undergoing slow displacement rates. Bedrock compositions on the slope has abundant mica schists, with a thrust faults emplacing more gneissic compositions on top. As part of a nationwide task by NGU, this study will focus on identifying some of the geomorphological signs on the slope, assess potential controlling mechanisms and address the hazard it poses. The field is complex with generally different scenes happening, and four scenarios has been identified on the slope related to deformational processes where one of them stand out as the bigger hazard. Stáluvárri can be seen influenced by normal faulting from post-Caledonian extension and rifting. Two larger fault systems can be seen in NW-SE and NE-SW fashion and is directly controlling the related rear rupture surfaces of the displaced material. Because of the sheer size of the slope, with inherited large fault systems controlling larger sections of the slope, it has been classified as being controlled deep-seated gravitational slope deformation, a landslide case which has slow displacement rates associated with it.